2001
DOI: 10.1007/s002210100785
|View full text |Cite
|
Sign up to set email alerts
|

Representation of the visual field in the lateral intraparietal area of macaque monkeys: a quantitative receptive field analysis

Abstract: The representation of the visual field in the primate lateral intraparietal area (LIP) was examined, using a rapid, computer-driven receptive field (RF) mapping procedure. RF characteristics of single LIP neurons could thus be measured repeatedly under different behavioral conditions. Here we report data obtained using a standard ocular fixation task during which the animals were required to monitor small changes in color of the fixated target. In a first step, statistical analyses were conducted in order to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

34
204
2
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(242 citation statements)
references
References 60 publications
34
204
2
2
Order By: Relevance
“…This finding is consistent with most electrophysiological studies of LIP and with the strong contralateral bias reported in an fMRI study (3,7,27,28; but see ref. 8).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This finding is consistent with most electrophysiological studies of LIP and with the strong contralateral bias reported in an fMRI study (3,7,27,28; but see ref. 8).…”
Section: Discussionsupporting
confidence: 91%
“…We also found a separate foveal representation in LIPv rostral to the peripheral field map. Previous electrophysiology studies placed the fovea dorsal to the peripheral field representation and concluded that LIP contained a coarse but contiguous retinotopic map of the contralateral field (3,7,14). However, our results are consistent with previous imaging studies reporting a rostral foveal representation (14,21) and with LIP/frontal eye field (FEF) connectivity studies demonstrating that rostral LIP projects to the ventral portion of FEF representing the fovea/parafovea and caudal LIP to the dorsal portion of FEF representing the periphery (2,35,36).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Likewise, we believe it is important to keep in mind that RFs in FEF and LIP have diameters of the order of 10-208 [e.g. 5,6] at eccentricities often used in human psychophysical experiments ( 108). The relevance of such experiments to remapping is questionable unless researchers ensure that stimuli are separated by at least the RF diameter distance.…”
mentioning
confidence: 99%